Pengaruh Lingkungan Keluarga, Kepribadian, Dan Motivasi Berwirausaha Terhadap Minat Berwirausaha Siswa Kelas XII Jurusan Bisnis Daring Dan Pemasaran SMK Negeri 1 Makassar - Joan Gabriella Palebangan; M Thamrin Tahir; Abd Rahim (Universitas Negeri Makassar, 2022)
The number of job seekers is not balanced with the available jobs resulting in increasing unemployment. Efforts made are entrepreneurship. Interest in entrepreneurship can grow because of the influence of the family environment, personality, and motivation. This research was conducted on grade XII students at the Department of Online Business and Marketing at SMKN 1 Makassar. The sampling technique employed the Slovin’s technique. The total population in this study was 103 students and the sample obtained was 82 students. This type of study was quantitative research and data collection techniques employed questionnaires. The data analysis technique employed descriptive analysis, multiple regression analysis, classical assumption test, multiple regression test, hypothesis testing, and coefficient of determination test. The results show that (1) there is a significant influence of the family environment on the entrepreneurship interest of grade XII students of Online Business and Marketing at SMKN 1 Makassar, (2) there is a significant influence between personality and interest in entrepreneurship of grade XII students of Online Business and Marketing at SMKN 1 Makassar, (3) there is a significant influence between motivation and interest in entrepreneurship in grade XII students of Online Business and Marketing at SMKN 1 Makassar, and (4) there is a significant influence between family environment, personality and motivation on entrepreneurship interest in grade XII students of Online Business and Marketing at SMKN 1 Makassar.